To Assess Platelet Indices in Type 2 Diabetic Patients with or Without Complications - Aayza Mujahid, Jawad Zaffar Choudry, Hamid Iqbal, Saafia Sartaj, Saadia Latif, Syeda Bint-E-Zahra, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The main feature of diabetes mellitus (DM), a complicated metabolic illness with significant global impact, is persistent hyperglycemia brought on by either insulin resistance or deficiency, or both. Aim: To assess platelet indices in type 2 diabetic patients with or without complications. Study Design: cross-sectional study. Methodology: This study was carried at Combine Military Hospital-Multan. Total patients (n=120) were enrolled and were divided into two equal groups with complication and without complication. In addition to providing standard follow-up care, the diabetes follow-up clinic screens all DM patients for diabetes-related complications at the initial visit. Patients were then checked for these issues every six months. The data was entered and analyzed in SPSS 23. Mean ± SD were given for numeric data i.e., age and platelet indices. The frequency and percent were calculated for categorical data i.e., gender. Independent sample t-test was used to compare the age and platelet indices between the two groups. Chi-square test was used to compare the gender distribution between the two groups. A p-value ≤ 0.05 was considered significant. Results: Independent sample t test revealed that there was no significant difference in mean age between both groups. The results revealed that the mean PDW, MPV, PLCR and PCT levels was significantly higher in patients with complicated diabetes. Practical implication: This study helped in exploring platelets indices as platelet indices results have notable impact on patient diagnosis and follow-up. With increasing demands and burden of patients in Hospital, new reliable and quick diagnosis is need of hour. Conclusion: It was concluded that all platelet indices like MPV, PDW, and P-LCR increased significantly in patients with complicated diabetes. However, platelet indices can be used as a simple, low-cost metric to track and gauge the likelihood of problems. Keywords: Diabetes Mellitus, Hyperglycemia, Platelet Indices, Complications and Hematological Parameters.